Media research in the 21st Century - Franklin, M. I. (Henry Stewart Talks, 2010)
The history of media research, Key debates and data-gathering techniques pertinent to both qualitative and quantitative modes of research, Choices about research method relates, Theoretical models, Data-gathering methods, Ideas about media and society along the spectrum that separates quantitative from qualitative research methods, Recent challenges to established ways of undertaking media research, Media convergence, The increasing importance of the Internet, Changing audiences, markets and business models that defy disciplinary and national borders, How 'new' and 'old' media co-exist and compete with one another
Archived at 2022/04/12